Modeling and Mathematical Analysis of Labor Force Evolution - Sanaa ElFadily; Abdelilah Kaddar (Modelling and Simulation in Engineering)
In this paper, we propose a delayed differential system to model labor force (occupied labor force and unemployed) evolution. The mathematical analysis of our model focuses on the local behavior of the labor force around a positive equilibrium position; the existence of a branch of periodic solutions bifurcated from the positive equilibrium is then analyzed according to the Hopf bifurcation theorem. Finally, we performed numerical simulations to illustrate our theoretical results.